ANALYSIS OF THE SUBJECT MATTER OF ART AND CULTURE CLASS III MI/SD, CONFORMITY OF CHARATERISTICS, HOTS, AND 4C - Pitriani, Siti (Sunan Kalijaga International Journal on Islamic Educational Research, 2021)
The analysis of the subject matter of Cultural and Arts and MI / Elementary Workshops conducted by the author aims to find out the relevance of the subject matter contained in the Thematic Book of teachers and class III students of the 2013 revised 2018 curriculum with the scope of the subject matter of Cultural Arts and MI / SD Crafts which includes competencies knowledge and skills, characteristics and development of MI / SD Art and Cultural Materials, analyzing KI-KD and their relevance to MI / SD Art and Cultural structure, characteristics of student development, HOTS, 4C (Critical Thinking, Creativity, Communication, Collaboration ), cultural and citizenship literacy and character education, and innovation. The method used is the type of library research. Collection and review of reference indicators for the analysis of the subject matter of Art and Culture and Grade III elementary / MI. The research method used is the type of library research. The results of the analysis state that the relevance of the scope of Culture and Arts and Crafts in Permendikbud number 21 2016 on Basic and Secondary Education Content Standards with the 2013 Revised 2018 Curriculum Student Book is considered to be relevant. Characteristics of Cultural Arts and MI / Elementary Workshops include aspects of fine arts, aspects of music, aspects of dance and aspects of skills. Characteristics of student development are in a concrete operational stage. Hots Distribution (Critical Thinking 24%, Problem Solving 9%, and Creative Thinking 67%). 4C distribution (Critical Thinking 23%, Communication 6%, Collaboration 8%, and Creativity 63%). Cultural and citizenship literacy as well as character education are listed in the subject matter of Cultural Arts and the Revised Workshop of 2018 books of teachers and class III students. The innovations offered in the learning of Arts and Culture and MI / SD Crafts are using interactive multimedia that is relevant to the development of science and technology in the era of the industrial revolution 4.0.